Laser Navigation Combined With XperCT Technology Assisted Puncture of Brainstem Hemorrhage - Wang, Qingbo; Guo, Wei; Zhang, Tao; Wang, Shuangquan; Li, Chenglong; Yuan, Zhengbo; Wei, Qi; Geng, Xin; Li, Zefu (Frontiers in Neurology, 2022)
Background Brainstem hemorrhage has a rapid onset with high mortality and disability rates. In recent years, an increasing number of studies have reported on the surgical treatment of brainstem hemorrhage. The introduction of stereotaxic instruments and navigation systems has improved the accuracy of surgical treatment; however, the popularity of these devices in the primary hospitals is not high. In this study, we introduce laser navigation combined with the XperCT technology to assist in the puncture and drainage of brainstem hemorrhage, aiming to improve surgical accuracy and facilitate the drainage of brainstem hemorrhage in primary hospitals. Material and Methods A total of five patients (four men and one woman), aged 34–70 years, who underwent hematoma puncture drainage with the assistance of laser navigation combined with XperCT technology at the Binzhou Medical University Hospital, China, between June 2020 and Aug 2021 were included in the study. The brainstem hemorrhages had volumes of 7–18 ml. Statistical analyses of the postoperative puncture deviation distance (distance between the actual puncture end and simulated puncture end) and postoperative improvement were also performed. Results The operations were successfully completed in all five patients. The puncture deviation distance was <6 mm in all five patients and <2 mm in two patients. The postoperative hematoma clearance rate was about 70%−90%. Among four patients with respiratory failure, three had improved breathing and resumed spontaneous breathing. Out of three patients with high fever, one showed a substantial decrease in body temperature. There were no cases of postoperative infection. Of the five patients, two recovered consciousness, one died, and two voluntarily gave up further treatment and were discharged. Conclusions Laser navigation combined with the XperCT technology could improve the accuracy of surgical puncture. The technique might be convenient for widespread clinical application because of its low trauma, high precision, short operation time, and low operation cost.